2019
DOI: 10.1002/jor.24275
|View full text |Cite
|
Sign up to set email alerts
|

Direct electromagnetic coupling for non‐invasive measurements of stability in simulated fracture healing

Abstract: Diagnostic monitoring and prediction of bone fracture healing is critical for the detection of delayed union or non‐union and provides the requisite information as to whether therapeutic intervention or timely revision are warranted. A promising approach to monitor fracture healing is to measure the mechanical load‐sharing between the healing callus and the implanted hardware used for internal fixation. The objectives of this study were to evaluate a non‐invasive measurement system in which an antenna electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Such an approach is pertinent to pediatric patients after procedures that would typically entail CT imaging, as radiation exposure should be curtailed to minimize risk of radiation-induced cancers ( 35 ). This idea has been explored of late in percutaneous devices to measure strain and tissue impedance ( 36 , 37 ), but emerging developments in passive and active devices could offer fully implantable, wireless embodiments ( 38 ). In addition, we obtained measurements in real-time while animals walked on a treadmill.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach is pertinent to pediatric patients after procedures that would typically entail CT imaging, as radiation exposure should be curtailed to minimize risk of radiation-induced cancers ( 35 ). This idea has been explored of late in percutaneous devices to measure strain and tissue impedance ( 36 , 37 ), but emerging developments in passive and active devices could offer fully implantable, wireless embodiments ( 38 ). In addition, we obtained measurements in real-time while animals walked on a treadmill.…”
Section: Discussionmentioning
confidence: 99%
“…To address these limitations, our research group has developed a diagnostic system capable of measuring temporal changes in the relative fracture callus stiffness for any fracture treated with standard off-the-shelf orthopaedic hardware stabilization devices, without the need to modify existing hardware design (50). This diagnostic relies upon fractures with orthopaedic implant fixation behaving as a composite structure, where stiffness of the healing fracture tissues and the implanted hardware both contribute to the stiffness of the composite structure.…”
Section: Introductionmentioning
confidence: 99%
“…Kienast et al [ 9 ] reported further clinical data from the same system and categorized patients into different healing patterns similar to Burny et al [ 22 ]. New device proposals are constantly upcoming [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] underlining the importance of the topic.…”
Section: Discussionmentioning
confidence: 99%